PENGARUH E-SERVICE QUALITY DAN HARGA TERHADAP LOYALITAS PELANGGAN BERRYBENKA DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Berrybenka di Kota Semarang) - Nina Rahma Sari; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2020)
This study aims to examined the effects of e-service quality and price to customer loyalty through customer satisfaction. Based on a survey conducted by Iprice.com it can be seen that the number of visitors to the Berrybenka website in the past two years has decreased. In 2017 the number of visitors to the Berrybenka website was 3.115.000 visitors. However, the following year Berrybenka experienced a decrease in the number of website visitors by 1.51.,300 visitors. Therefore, the number of visitors to the Berrybenka website in 2018 will be 1.597.700 visitors. The population is consumers who have bought Berrybenka products, while the sample is 100 respondents with certain criteria carried out.The analysis used in this research is linear regression analysis using IBM SPSS 21.0 and mediation test (sobel test) to test the mediating effect of the intervening variable. The results of this study indicate that e-service quality and price have a partial and simultaneous effect on customer satisfaction, where when together price has the greatest influence on customer satisfaction.based on the Mediation test using the sobel test, the customer satisfaction variable can mediate the effect of e-service quality on customer loyalty insignificantly and can be said as a full mediated, as well as the variable customer satisfaction mediated the effect of price of customer loyalty significantly and can be said to be a partial mediating variable.